Emerging trends and issues in management consulting : consulting as a Janus-faced reality - Buono, Anthony F. (Emerald Publishing Limited : IAP, 2009)
The ninth volume in the Research in Management Consulting (RMC) series--much like the volumes that preceded it--underscores that management consulting is a multifaceted field with a truly eclectic nature. Management consultants range from sole practitioners and those working in small boutique firms to members of global consultancies that literally span the world. Their interventions can consist of relatively simple, commonly available services focused on mid- to lower level organizational members, to those that are far more esoteric in nature, providing vital assistance and direction to key players at the upper echelons of the corporate hierarchy. As consultants we can have individuals, groups and work units, or organizations as our "client," and engagements can be dominated by junior-level specialists or guided by senior-level gurus and advisors.The volume contains 11 chapters that continue the RMC series' commitment to enhancing our understanding of and insight into management consulting and the consulting process from a cross-cultural, global perspective. The book is divided into three sections that explore emerging issues and challenges in the management consulting industry, trends and techniques in management consulting interventions, and reflections on consulting and the consulting process.This volume, which captures the dual nature--possibilities and challenges -- associated with management consulting, adds to the Janus-faced portrayal of the field. Drawing on the interplay between practice and scholarship, the volume adds to the series goal of gaining a fuller understanding of management consulting theory in practice and practice in context in a quest for actionable knowledge about consultants, consultancies and the consulting process.
Keywords: Business consultants.; Consulting firms.; Management.; Business & Economics -- Consulting.; Consultancy.; elektronické knihy; electronic books